2014
DOI: 10.1039/c3ee43048k
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemistry of core–shell tandem junction n–p+-Si/n-WO3microwire array photoelectrodes

Abstract: Tandem junction (n-p + -Si/ITO/WO 3 /liquid) core-shell microwire devices for solar-driven water splitting have been designed, fabricated and investigated photoelectrochemically. 0.0068% and 0.0019% when the cathode compartment was saturated with Ar or H 2 , respectively, due to the non-optimal photovoltage and band-gap of the WO 3 that was used in the demonstration system to obtain stability of all of the system components under common operating conditions while also insuring product separation for safety pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
159
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 169 publications
(162 citation statements)
references
References 36 publications
0
159
0
3
Order By: Relevance
“…[55] However, challenges include the increased complexity of epitaxial growth on the nontraditional crystallographic surface terminations present, as has been used for state-of-the-art planar designs, and the increased fabrication complexity, in general.…”
Section: Microwire and Microstructured Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…[55] However, challenges include the increased complexity of epitaxial growth on the nontraditional crystallographic surface terminations present, as has been used for state-of-the-art planar designs, and the increased fabrication complexity, in general.…”
Section: Microwire and Microstructured Designsmentioning
confidence: 99%
“…Similar absorber-inmembrane architectures that incorporate semiconducting microwires have also been proposed, where the electrical connectivity of the device is achieved through the microwires that cross through the membrane. [55,74] Recent modeling studies have also provided guidelines for the design of efficient vapor-fed solar-hydrogen devices, where the ionomer encapsulates the photoelectrochemical components (Figure 4 d2). Critical device dimensions that lead to optimal water, hydrogen, and oxygen transport have been identified in various cell configurations.…”
Section: Vapor-feed Designmentioning
confidence: 99%
“…11−13 For example, Shaner et al reported a n-p(+)-Si/n-WO 3 microwire junction obtained by successive vacuum deposition of BCl 3 to achieve Si p-doping, DC sputter coating of an ITO ohmic contact, and electrodeposition of n-WO 3 , followed by annealing at 400°C for 2 h. The device supported overall water splitting with 0.0019% solar to hydrogen (STH) efficiency. 12 Recently, there is also increasing interest in tandem junctions formed between suspended semiconductor particles. Such tandem or "z-scheme photocatalysts" usually employ soluble redox couples for charge transfer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…81 Under this condition the initial potential required to impart water splitting was also not 1.229 V but rather approached ÀN V because no H 2 was present and therefore E bias -N V. It is often assumed that during rapid water splitting under an ambient atmosphere, enough H 2 and O 2 exist near the surface of the electrodes (or particles) so that generally the standard potential, E 0 fuel , is an accurate approximation of E fuel . 82 It is unclear if this approximation holds when H 2 and/or O 2 are present at reduced partial pressures. To assess whether particle suspensions are suitable for use in an actual solar PEC water-splitting reactor, they should be evaluated in the presence of H 2 at 1 bar pressure above the HER reactor and O 2 at 1 bar pressure above the OER reactor.…”
Section: (B) Bias Assistancementioning
confidence: 99%